2015
DOI: 10.1039/c4mt00287c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-toxic zinc exposure on human epidermal keratinocytes

Abstract: Zinc is an essential microelement; its importance to skin is shown by severe skin symptoms in hereditary or acquired zinc deficiency, by the improvement of several skin conditions using systemic or topical zinc preparations and by the induced intracellular zinc release upon UVB exposure, which is the main harmful environmental factor to skin. Understanding the molecular background of the role of zinc in skin may help to gain insight into the pathology of skin disorders and to provide evidence for the therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…This is in accordance with a recently reported effect of Zn on human epidermal keratinocytes HaCaT [22]. Melanocytes are thought to form stable populations with a very low rate of proliferation which is associated with specific changes in cell cycle control elements [23].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in accordance with a recently reported effect of Zn on human epidermal keratinocytes HaCaT [22]. Melanocytes are thought to form stable populations with a very low rate of proliferation which is associated with specific changes in cell cycle control elements [23].…”
Section: Discussionsupporting
confidence: 77%
“…Although generally positive for cells, such sustained mitochondrial activity may represent a challenge regarding the functional integrity of these same cells, particularly in circumstances in which this activity may contribute to the overwhelming of antioxidant defense systems and the induction of chronic oxidative stress. We have not focused on specific elements of ROS-dependent signaling here; nevertheless, it may be presumed that these elements were also involved, particularly in consideration of a similar study on epidermal keratinocytes [22]. In contrast, we did not observe similar mitochondria-stimulating effects of external Zn in melanoma cells, a finding which might be explained by the already existing high activity of this compartment or by the rapid buffering of free intracellular Zn levels, as is suggested at least somewhat by the less significant elevation of these levels in the exposed melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sedimentation of the particle is a problem for the cell viability assay only at the highest concentration and does not hinder our conclusions concerning the biological effect of Zn-HAp. However, the positive effect on cell survival observed for Zn:HAp with x Zn = 0.05 could be due to a higher release of Zn(II) ions that are known to stimulate cell proliferation at concentrations in the 100 µM range [44]. …”
Section: Resultsmentioning
confidence: 99%
“…(Poss and Tonegawa, 1997) In response to the oxidative stress, antioxidant enzymes, including glutathione and superoxide dismutase were upregulated. Others have demonstrated that zinc exposure causes an increase in reactive oxygen species and nitric oxide, while depleting glutathione, and thereby causing cell death (Bishop et al, 2007; Chen and Liao, 2003; Emri et al, 2015; Kim and Koh, 2002; Pong et al, 2002; Seo et al, 2001; Takeyama et al, 1995). Since similar patterns of up-regulated genes were observed in Odora cells exposed to zinc, biochemical assays measuring intracellular glutathione and hydrogen peroxide levels in Odora cells exposed to zinc for 6, 12, and 24 h were performed.…”
Section: Discussionmentioning
confidence: 99%